PERUBAHAN KADAR SENYAWA BIOAKTIF DAN AKTIVITAS ANTIOKSIDAN BERAS ORGANIK MERAH VARIETAS LOKAL DALAM KEMASAN POLIPROPILEN DENGAN VARIASI LAMA PENYIMPANAN - Monika, Pricila; Widyawati, Paini Sri; Sutedja, Anita Maya (Widya Mandala Surabaya Catholic University, 2014)
The increasing of health awareness in the society motivated them to consume food that gives values in health, such as organic rice (Oryza sativa L.). Nowadays, red rice became very popular because of their healthy benefit as source of antioxidant. Red rice Saodah variety is the most developed colored rice in Sleman, Yogyakarta. The shelf life of colored rice is around six months. During storage the bioactive compounds and antioxidant activities of the red rice will be changed. One way to inhibit that changes is by using polypropilen (PP) as packaging. The results showed that storage time increased the yield, bioactive content, and antioxidant activity of red rice, but decreased the total anthocyanin. The highest yield of the red rice is in the 4th month (11.86±0.04%) but after that will be decreased. The highest total phenolic (21.49±1.21 mg GAE/g) and total flavonoid (4.38±0.29 mg CE/g) is in the 5th month and decreased in the 6th month. The highest iron reducing power (39.53±6.05 mg GAE/g) is in the 4th month and decreased in the 5th and 6th month, and free radical scavenging activity increased until the 3rd month (1.81±0.16 mg GAE/g) and after that will be decreased.